2008
DOI: 10.1007/s00497-008-0079-7
|View full text |Cite
|
Sign up to set email alerts
|

Calcium changes during megasporogenesis and megaspore degeneration in lettuce (Lactuca sativa L.)

Abstract: Potassium pyroantimonate was used to localize loosely-bound calcium in young ovules of lettuce (Lactuca sativa L.) during megasporogenesis to investigate the relationship between ionically available calcium and megaspore degeneration. At the megasporocyte (megaspore mother cell) stage, few calcium precipitates were located in the ovule. Following meiosis in the megasporocyte, a linear tetrad of four megaspores is formed, with three of the four megaspores degenerating from the micropylar end inward. Only the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…First, the earliest visible evidence of functional divergence between the receptive and the persistent synergid are changes in the labeling pattern of loosely bound calcium, which precede by almost a day to the outwardly visible degenerative changes in the cytoplasm of the receptive synergid (Tian and Russell 1997). Second, in megasporogenesis, abortive megaspores show a depletion of loosely bound calcium immediately prior to visible changes in their cellular ultrastructure (Qiu et al 2008). Changes in loosely bound calcium may therefore precede evident [Ca 2? ]…”
Section: Ca 2? Distribution In the Stigmamentioning
confidence: 98%
“…First, the earliest visible evidence of functional divergence between the receptive and the persistent synergid are changes in the labeling pattern of loosely bound calcium, which precede by almost a day to the outwardly visible degenerative changes in the cytoplasm of the receptive synergid (Tian and Russell 1997). Second, in megasporogenesis, abortive megaspores show a depletion of loosely bound calcium immediately prior to visible changes in their cellular ultrastructure (Qiu et al 2008). Changes in loosely bound calcium may therefore precede evident [Ca 2? ]…”
Section: Ca 2? Distribution In the Stigmamentioning
confidence: 98%
“…Although AGP17 and AGP19 are also expressed in the developing gynoecium of Arabidopsis (Acosta-García and Vielle-Calzada, 2004), a possible redundant function of AGP18 with these closely related genes encoding AGPs remains to be investigated, although the scarcity of insertions in AGP18 suggests a nonredundant role for these proteins in the female gametophyte. Recently, cytokinin signaling has been implicated in the specification but not the selection of the Arabidopsis FM (Cheng et al, 2013), and previous results showed that processes involving protease activity (Chen et al, 2008), calcium concentration (Qiu et al, 2008), and callose deposition (Rodkiewicz, 1970;Webb and Gunning, 1990) are associated with megaspore degeneration, although their role is not understood. Determining if AGP18 mediates megaspore selection through regulatory controls that include some of these processes will require additional studies.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the relationship between calcium levels and megaspore death in lettuce (Lactuca sativa L.) ovules, free Ca 2+ levels were examined by histological staining with potassium pyroantimonate (Qiu et al 2008). Calcium precipitates were rarely detected in the cytoplasm and nucleus of the MMC, but accumulated to similar levels in the linear tetrad of megaspores after meiosis.…”
Section: Other Factors Influencing Megaspore Fatementioning
confidence: 99%
“…Interestingly, during the sequential degeneration of the three most micropylar megaspores, calcium precipitates were observed in the cytoplasm but not the nucleus of the degenerating spore, followed by an increase in calcium levels in the nucleolar vacuole of the adjoining megaspores. After degeneration of the last nonfunctional megaspore, numerous calcium precipitates were noted in the cytoplasm and nucleus of the functional megaspore (Qiu et al 2008). Although the functional relevance of these changes in calcium distribution is uncertain, the flux of free calcium into the degenerating spores appears to foreshadow imminent degeneration, suggesting that Ca 2+ may play a role in signalling between the megaspores.…”
Section: Other Factors Influencing Megaspore Fatementioning
confidence: 99%